2021
DOI: 10.12998/wjcc.v9.i12.2703
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal lymphadenopathy in COVID-19: A review of literature

Abstract: A novel coronavirus disease 2019 (COVID-19) is a progressive viral disease that affected people around the world with widespread morbidity and mortality. Patients with COVID-19 infection typically had pulmonary manifestation but can also present with gastrointestinal, cardiac, or neurological system dysfunction. Chest imaging in patients with COVID-19 commonly show bilateral lung involvement with bilateral ground-glass opacity and consolidation. Mediastinal lymphadenopathy can be found due to infectious or non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Meta-analysis revealed 3.38% of patients had a presentation of lymphadenopathy on CT scan [1]. The size of the lymph nodes is a strong predictor of etiology with 15 mm or less more likely reactive and larger than 25 mm likely pathologic due to malignancy or sarcoidosis [5]. Since cardiac and pulmonary lymphatic drainage is to the mediastinal lymph nodes, it would be reasonable to assume that these lymph nodes enlargement will be more likely when both organs are involved or if there is a severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis revealed 3.38% of patients had a presentation of lymphadenopathy on CT scan [1]. The size of the lymph nodes is a strong predictor of etiology with 15 mm or less more likely reactive and larger than 25 mm likely pathologic due to malignancy or sarcoidosis [5]. Since cardiac and pulmonary lymphatic drainage is to the mediastinal lymph nodes, it would be reasonable to assume that these lymph nodes enlargement will be more likely when both organs are involved or if there is a severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been found that the district where the person lives and smoking history are associated with the occurrence of MLNE. MLNE is not the typical chest CT finding in COVID-19 pneumonia 10 . However, atypical findings such as MLNE are associated with the prognosis of patients with COVID-19 11 .…”
Section: Introductionmentioning
confidence: 90%
“…The incidence of MLNE in patients with COVID-19 pneumonia is 0%-66%, and the relationship between CT findings has not been demonstrated in the literature yet 10 . The higher mortality rate in hospitalized COVID-19 patients with MLNE than those without MLNE suggested that it should be investigated as a prognostic factor for serious disease 12 .…”
Section: Introductionmentioning
confidence: 95%
“…All CT images were reviewed and evaluated by expert radiologists. The criterion for significant lymph node enlargement of mediastinal lymph nodes was considered a short-axis dimension ≥10 mm ( 22 ). Information of 213 patients was recorded, including demographic characteristics, clinical symptoms, underlying diseases, and laboratory findings.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have recently suggested that mediastinal lymphadenopathy (LAP) prevalence in patients with COVID-19 ranges from 3•4% to 5•4%, while its prevalence in patients with severe COVID-19 has been seen a sharp rise to 66% ( 14 , 18 , 19 ). Three retrospective studies in China reported a prevalence of mediastinal lymphadenopathy in 43.5%, 41.7%, and 19.8% of 154, 192, and 499 patients with COVID-19, respectively ( 20 22 ). Also, lymphadenopathy at admission was significantly more common in patients who died during hospitalization than those discharged ( 23 ) and was associated with increased mortality ( 24 ).…”
Section: Introductionmentioning
confidence: 99%